Stay out (almost) all night: contrasting responses in flight activity among tropical moth assemblages - Lamarre, G. P. A.; Mendoza, I. [UNESP]; Rougerie, R.; Decaens, T.; Herault, B.; Beneluz, F. (Entomological Soc Brasil, 2015)
Variations in diel activity among hyperdiverse tropical communities of moths, despite representing a key component of niche partitioning between species, have barely been studied so far. Using light trapping from dawn to sunset over a 1-year period in French Guiana, we investigated these variations within and between two families of moths (Sphingidae and Saturniidae). Our results revealed contrasting patterns in flight activity at night between Sphingidae and Saturniidae. Sphingidae reached their peak in species richness and abundance between 7:00 and 8:00 p.m., followed by a decrease around 11:00 p.m. to midnight, whereas Saturniidae were continuously present throughout the night, with a peak around midnight. In addition, we found changes in diel activity among some of the most common genera in each family, highlighting distinct behavioral, physiological, and functional traits among taxa. Given differences in flight activity at different taxonomic levels, it is strongly recommended to monitor by light trapping throughout the night to effectively sample saturniid and sphingid assemblages, even though the activity of Sphingidae sharply declines after midnight. These results improve the general natural history information of tropical moths and reinforce the need of further research on the ecological and taxonomic consequences of differences in diel activity.
Keywords: Behavior; Diel activity; Monitoring; Moth; Light trap; Tropical forest